Edukasi dan Bimbingan Terhadap Para Remaja Putri Tentang “Hukum-Hukum Haidl” Di Desa Pranggang Kediri - Alfin Lailatul Mufarichah; Siti Kalimah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Many of the young women who have experienced menstruation, but do not know the laws of menstruation. Most of them only get a little lesson from their parents because their parents also lack understanding about the laws of menstruation. Based on that context, educational and guidance programs for young women on "Menstrual laws". This educational and guidance activity is seen as quite successful in educating and guiding young women in this environment. In mentoring also emerged good cooperation and communication between researchers and the people of Pranggang Village Plosoklaten District Kediri Regency. The number of participants who follow the education and guidance of menstrual problems is also a success of this program. All participants are facilitated with a photocopy of the menstrual module that is shared for free. The success of this program can also be used as a model of implementing religious reinforcement elsewhere by adjusting the existing context.